Collaboration for Knowledge Creation in Nepalese Hospitality Industry (The International Research Journal of Management Science, 2018)
This paper examines the different factors promoting collaboration for knowledge creation in the hospitality industry such as hotel, travel and trekking agencies. The study is based on primary data with 382 responses. The self-administered questionnaires were used to collect the perceptive opinions from the respondents. The study concludes that hospitality industry employees’ supportive and participative behaviour and keep each other informed about work-related issues in the team have a larger impact on the knowledge creation while each employee contributes equally to the organisation’s service innovation influences less.